Reforestation of ‘Village Forest’ to Improve Sustaiability Creative Industries in Desa Siponjot - Vinolina, Noverita Sprinse; Sipayung, Antonio Marro; Dardanila; Pintauli, Sondang (Talenta Publisher, 2020)
This program is conducted to assist Siponjot Village while empowering the people of Siponjot Village to be able to utilize and maximize the benefit of the village forest. Village forest might support the availability of raw materials required for making musical instruments, such as high quality of wood, including how to process wood waste from making musical instruments to be used as creative souvenirs and improve the economic value. The raw material for production determined its results of the production of wood-based musical instruments. Thus, in order to produce a high quality tanginang, hasapi, and gondang, which previously began to be produced by arts crafts in the Sitangkubang area of ​​Siponjot Village, a high quality of raw materials is needed. The community service team surveyed the location of planting seeds for village forest restoration, provided socialization related to the importance of village forest cultivation and the suitability of the Siponjot Village area for the cultivation of these plants. Village forest restoration aims to maintain the beauty and beauty of the village. Implementation of village reforestation activities starting from socializing forest tourism and the strength of village forests to the community, followed by a discussion about village forest management and its economic benefits. Handover of a thousand units of forest plant seedlings given to the villagers of Siponjot as part of the forest restoration program in the area.